Herderlike bediening aan die kind uit 'n egskeidingsgesin - SP van der Schyff; CHJ Venter (Acta Theologica)
In this article attention is paid to three aspects concerning the above mentioned theme. Firstly, basis-theoretical perspectives are developed on a child in a crisis situation. Secondly and investigation is undertaken on metatheoretical level on the child's unique emotional experience of the divorce of his or her parents. Aspects dealt with here are reactions of shock, grief, confusion, aggression, fear, feelings of guilt, loneliness, stress and feelings of inferiority. Finally, practice-theoretical guidelines are proposed for pastoral care to a child exposed to a divorce in his/her family. Special attention is paid to the functioning on a practical level of the pastoral basis attitude, the acts of listening to a child, Scripture reading, proclamation and prayer.